Improving Student Learning Outcomes in Al-Qur'an Hadith Learning through the Index Card Match Model at MIS NU Setia Mukti - Juju Julianti; Julhida (Journal of Action Research in Islamic Education, 2025)
The learning outcomes of the Al-Qur'an Hadith material "Meaning and Content of Q.S. Al-'Adiyat" of class V students of MIS NU Setia Mukti Kurungan Nyawa II, Buay Madang District, East OKU Regency, out of 20 students who achieved the Minimum Completion Criteria (KKM) were 6 students or only 30% while 14 students or 70.00% had not achieved the results expected by the class V teacher of MIS NU Setia Mukti Kurungan Nyawa II, Buay Madang District, East OKU Regency who targeted an average classical completion value of 87.50% or equal to 19 students. One of the contributing factors is the use of inappropriate learning models. Efforts to improve student learning outcomes through the Index Card Match model. The selection of the Index Card Match model is one of the right alternatives in improving understanding and increasing student creativity. Therefore, educators are needed who are able to improve and develop students in communicating both students with educators and educators with. This research was conducted for 3 weeks, from February to March 2024. The implementation of cycle I was carried out on February 18, 2024, cycle II on February 25, 2024, and cycle III was carried out on March 12, 2024. The subjects of this study were 20 students of class V MIS NU Setia Mukti Kurungan Nyawa II, Buay Madang District, East OKU Regency, consisting of 10 males and 10 females and having varying levels of ability. The results of learning improvements in cycle I, cycle II, and cycle III have achieved the results expected by the teacher with an average value of cycle III, the average student value reached 80.13 with a completion rate of 100%. This proves that the Index Card Match model can improve learning outcomes for the Al-Qur'an Hadith Subject Material "Meaning and Content of Q.S. Al-'Adiyat" in Class V MIS NU Setia Mukti.